GT Factor ZmGT-3b Is Associated With Regulation of Photosynthesis and Defense Response to Fusarium graminearum Infection in Maize Seedling - Zhang, Qianqian; Zhong, Tao; E, Lizhu; Xu, Mingliang; Dai, Weixing; Sun, Shuchang; Ye, Jianrong (Frontiers in Plant Science, 2021)
It is of critical importance for plants to correctly and efficiently allocate their resources between growth and defense to optimize fitness. Transcription factors (TFs) play crucial roles in the regulation of plant growth and defense response. Trihelix TFs display multifaceted functions in plant growth, development, and responses to various biotic and abiotic stresses. In our previous investigation of maize stalk rot disease resistance mechanism, we found a trihelix TF gene, ZmGT-3b, which is primed for its response to Fusarium graminearum challenge by implementing a rapid and significant reduction of its expression to suppress seedling growth and enhance disease resistance. The disease resistance to F. graminearum was consistently increased and drought tolerance was improved, while seedling growth was suppressed and photosynthesis activity was significantly reduced in the ZmGT-3b knockdown seedlings. Thus, the seedlings finally led to show a kind of growth–defense trade-off phenotype. Moreover, photosynthesis-related genes were specifically downregulated, especially ZmHY5, which encodes a conserved central regulator of seedling development and light responses; ZmGT-3b was confirmed to be a novel interacting partner of ZmHY5 in yeast and in planta. Constitutive defense responses were synchronically activated in the ZmGT-3b knockdown seedlings as many defense-related genes were significantly upregulated, and the contents of major cell wall components, such as lignin, were increased in the ZmGT-3b knockdown seedlings. These suggest that ZmGT-3b is involved in the coordination of the metabolism during growth–defense trade-off by optimizing the temporal and spatial expression of photosynthesis- and defense-related genes.